TINDAKAN PIDANA MATI TERHADAP HAK ASASI MANUSIA (ANALISIS PADA TERDAKWA KASUS NARKOTIKA DI INDONESIA) - Rizky Yudi Pradipta; Rumainur (INTELIGENSIA MEDIA, 2022)
In 2010 the General Assembly of the United Nations (UN) voted for 109 countries to approve the death penalty. Still, 41 countries did not agree based on the decision, one of which was Indonesia. To break the narcotics network in Indonesia, the application of severe punishment in the form of the death penalty is carried out as a preventive measure. The State of Indonesia established these rules in the 1945 Constitution, which is the legal basis for implementing state life and the welfare of the Indonesian people. However, implementing the death penalty contains different views from various groups. These factors include law enforcers who are not firm and social conditions that do not support and involve human rights. This study will use the method of normative juridical that researchers will analyze based on secondary data, which includes books, previous research, and news. The data analysis technique in this study is called